(untitled)
We compute Bott Chern, and Aeppli cohomology for a complex structure on the six sphere, S^6.We also give a table for the hodge numbers for the Bott-Chern (and thus also Aeppli) cohomology where hodge numbers are given in terms of whole number parameters a = h_^2,0-h_^1,0, c = h_^0,2,d = h_^1,2, h_^2,0, h_BC^1,1, and h_BC^2,2. As an example, we work out the Bott-Chern hodge numbers completely in the hypothetical case that the Dolbeault cohomology has h^2,0 = a = c = d =0. , number=3, journal=European Journal of Pure and Applied Mathematics, year=2017, month=Apr., pages=440–454